Effects of the Angiotensin Receptor Blocker Olmesartan on Adipocyte Hypertrophy and Function in Mice with Metabolic Disorders. (2nd June 2014) - Maeda, Akinobu; Tamura, Kouichi; Wakui, Hiromichi; Ohsawa, Masato; Azushima, Kengo; Uneda, Kazushi; Kanaoka, Tomohiko; Kobayashi, Ryu; Ohki, Kohji; Matsuda, Miyuki; Tsurumi-Ikeya, Yuko; Yamashita, Akio; et al.
Abstract : In the present study, we examined the therapeutic effects of olmesartan, an angiotensin II (Ang II) type 1 receptor (AT1R)-specific blocker, in genetically obese diabetic KKAy mice, a model of human metabolic disorders with visceral obesity, with a focus on an olmesartan effect on the adipose tissue. Olmesartan treatment (3 mg/kg per day) for 4 weeks significantly lowered systolic blood pressure but did not affect body weight during the study period in KKAy mice. However, there were three interesting findings possibly related to the pleiotropic effects of olmesartan on adipose tissue in KKAy mice: (1) an inhibitory effect on adipocyte hypertrophy, (2) a suppressive effect on IL-6 gene expression, and (3) an ameliorating effect on oxidative stress. On the other hand, olmesartan exerted no evident influence on the adipose tissue expression of AT1R-associated protein (ATRAP), which is a molecule interacting with AT1R so as to inhibit pathological AT1R activation and is suggested to be an emerging molecular target in metabolic disorders with visceral obesity. Collectively, these results suggest that the blood pressure lowering effect of olmesartan in KKAy mice is associated with an improvement in adipocyte, including suppression of adipocyte hypertrophy and inhibition of the adipose IL-6-oxidative stress axis. Further study is needed to clarify the functional role of adipose ATRAP in the pleiotropic effects of olmesartan.